Population pharmacokinetics of sirolimus in Chinese adult liver transplant recipients: a retrospective study. (2nd December 2021) - Zhang, Yang; Zhang, Xuanling; Zou, Yue; Sun, Yiqi; Li, Xingang
Abstract: Considering the significant interindividual variability and a narrow therapeutic index, we aimed to determine the population pharmacokinetics (PPK) of sirolimus and identify the factors in Chinese adult liver transplant recipients. Data were retrospectively extracted from adult liver transplant recipients receiving sirolimus in our hospital. The trough blood concentration data, obtained from traditional therapeutic drug monitoring-based dose adjustments, were used to develop a population pharmacokinetic model by non-linear mixed-effects modelling (NONMEM). The effect of demographic features, biological characteristics and concomitant medications was measured. The final model was verified by visual prediction check (VPC), bootstrap, and simulation. One hundred and sixteen blood concentrations from 63 patients were analysed. The PPK of sirolimus could be described by a one-compartment model with first-order absorption. Covariate analysis indicated that voriconazole co-therapy significantly decreased the oral clearance (CL) of sirolimus. The results of VPC and Bootstrap demonstrated that the final pharmacokinetic model adequately predicted observed concentrations. The simulation results showed that the dosage regimen of sirolimus should be reduced to 0.25 ∼ 0.45 mg/day for adult liver transplant recipients co-administered with voriconazole. The present study developed and validated a sirolimus PPK model for Chinese adult liver transplant recipients, and voriconazole co-therapy was found to be a significant covariate in the model. These results provide important information for clinicians to optimise the treatment regimens of sirolimus in Chinese adult liver transplant recipients.